miR-150 Suppresses the Proliferation and Tumorigenicity of Leukemia Stem Cells by Targeting the Nanog Signaling Pathway - Xu, Dan-dan; Zhou, Peng-jun; Wang, Ying; Zhang, Yi; Zhang, Rong; Zhang, Li; Chen, Su-hong; Fu, Wu-yu; Ruan, Bi-bo; Xu, Hai-peng; Hu, Chao-zhi; Tian, Lu; et al. (Frontiers in Pharmacology, 2016)
Proliferation, a key feature of cancer cells, accounts for the majority of cancer-related diseases resulting in mortality. MicroRNAs (miRNAs) plays important post-transcriptional modulation roles by acting on multiple signaling pathways, but the underlying mechanism in proliferation and tumorigenicity is unclear. Here, we identified the role of miR-150 in proliferation and tumorigenicity in leukemia stem cells (LSCs) (CD34+CD38- cells). miR-150 expression was significantly down-regulated in LSCs from leukemia cell lines and clinical samples. Functional assays demonstrated that increased miR-150 expression inhibited proliferation and clonal and clonogenic growth, enhanced chemosensitivity, and attenuated tumorigenic activity of LSCs in vitro. Transplantation animal studies revealed that miR-150 overexpression progressively abrogates tumour growth. Immunohistochemistry assays demonstrated that miR-150 overexpression enhanced caspase-3 level and reduced Ki-67 level. Moreover, luciferase reporter assays indicated Nanog is a direct and functional target of miR-150. Nanog silencing using small interfering RNA recapitulated anti-proliferation and tumorigenicity inhibition effects. Furthermore, miR-150 directly down-regulated the expression of other cancer stem cell factors including Notch2 and CTNNB1. These results provide insights into the specific biological behaviour of miR-150 in regulating LSC proliferation and tumorigenicity. Targeting this miR-150/Nanog axis would be a helpful therapeutic strategy to treat acute myeloid leukemia.